1965
DOI: 10.1063/1.1696902
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum, Dipole Moment, and Ring-Puckering Vibration of β-Propiolactone

Abstract: The microwave spectrum of β-propiolactone has been observed in the vibrational ground state and in the first four excited states of the ring-puckering vibrational mode. The variation of the rotational constants with vibrational quantum number and the relative intensities of the observed vibrational satellites indicate that the vibration is essentially harmonic with ν0=160 cm−1 and with no appreciable barrier at the planar configuration. The dipole moment is 4.17±0.03 D, with μa=3.67±0.03 D, μb=1.99±0.02 D, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…The spectroscopic constants obtained in this work provide an excellent description of the observed rotational spectrum as many of the m obs-calc residuals reported in Table 1 are smaller than ±1 kHz. The parameters determined in this study are compared with those reported earlier by Boone et al [5] in Table 2. The estimated accuracy of the rotational constants in the current study is <3 kHz which is two orders of magnitude lower than that reported previously (±0.2 MHz) and thus, the higher resolution FTMW spectrum has led to an improved determination of the ground state of b-propiolactone.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The spectroscopic constants obtained in this work provide an excellent description of the observed rotational spectrum as many of the m obs-calc residuals reported in Table 1 are smaller than ±1 kHz. The parameters determined in this study are compared with those reported earlier by Boone et al [5] in Table 2. The estimated accuracy of the rotational constants in the current study is <3 kHz which is two orders of magnitude lower than that reported previously (±0.2 MHz) and thus, the higher resolution FTMW spectrum has led to an improved determination of the ground state of b-propiolactone.…”
Section: Discussionmentioning
confidence: 78%
“…Based on the rotational constants of Boone et al [5], a total of 19 microwave transitions have been measured for b-propiolactone between 7 and 21 GHz. Several of these were measured for the first time.…”
Section: Microwave Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the completely optimized ground state structure are given in A-electron diffractions [6]; B-microwave spectroscopy [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…The dipole moment in the gas phase is 4.17 D [8,9] with components pa = 3.67 f 0.03, = 1.99 f 0.02, pc = 0, where a, b, and c are the principal axes of the inertia tensor, with c perpendicular to the ring plane and a directed along the 01=C2 bond.…”
Section: Previous Experimental and Theoretical Workmentioning
confidence: 99%